2016
DOI: 10.1002/cjce.22389
|View full text |Cite
|
Sign up to set email alerts
|

Sorption equilibrium and kinetics for cyclohexane, toluene, and water on Athabasca oil sands solids

Abstract: The sorption of solvents from the vapour phase to solid substrates is important in producing heavy oil and bitumen, particularly from the oil sands. We investigated the sorption and desorption equilibrium and kinetics of cyclohexane, toluene, and water on kaolinite, fine solids, and organic‐rich fine solids isolated from Athabasca oil sands over a wide range of solvent vapour concentrations using a gravimetric method. The isotherms for both adsorption and desorption of solvent vapour were determined, and the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 83 publications
4
15
0
Order By: Relevance
“…At low relative humidity, most of the water evaporates, while at 90 % relative humidity about 2/3 of the water is removed after 60 min. All of the water concentrations reported in Figure are well above equilibrium levels, based on the data of Tan et al, ranging from 1.5 times the equilibrium concentration at 40 % relative humidity to 6 times at 90 % relative humiduty. Despite the higher vapour pressure of cyclohexane, its residual concentrations did not drop significantly as the water evaporated.…”
Section: Influence Of Relative Humiditysupporting
confidence: 56%
See 1 more Smart Citation
“…At low relative humidity, most of the water evaporates, while at 90 % relative humidity about 2/3 of the water is removed after 60 min. All of the water concentrations reported in Figure are well above equilibrium levels, based on the data of Tan et al, ranging from 1.5 times the equilibrium concentration at 40 % relative humidity to 6 times at 90 % relative humiduty. Despite the higher vapour pressure of cyclohexane, its residual concentrations did not drop significantly as the water evaporated.…”
Section: Influence Of Relative Humiditysupporting
confidence: 56%
“…Interestingly, in the second stage, the average drying rate of cyclohexane (∼1.7 mg/kg/min) is much lower than the average drying rate of water (470 mg/kg/min, from total sample mass loss between 20 and 70 min at 30 % RH in the fume hood). All of the residual cyclohexane concentrations in Table and Figure are far in excess of equilibrium levels, based on the desorption isotherms reported by Tan et al for oil sands solids. Even if all of the mass loss at 20 min of drying (Figure ) was due to cyclohexane, the concentration in the vapour phase would be so low that the equilibrium concentration in the gangue would be ∼3 mg/kg.…”
Section: Influence Of Relative Humiditysupporting
confidence: 51%
“…Also, the increase of cation exchange capacity and layer charge density was reported to increase both the clay–organic interactions and the amount of organics retained. The results suggested a role for clays in enhancing solvent retention by trapping solvent in the adsorbed bitumen components and a correlation between solid surface characteristics and the amount of organics retained. …”
Section: Solvent Recoverymentioning
confidence: 94%
“…Although fines are a minority constituent, they have high surface-to-volume ratios and retain organic materials (e.g., residual bitumen), making solvent recovery problematic. A couple of studies observed that solvent vapor had a higher sorption rate and quantities on bare kaolinite than on bare quartz sand, due the larger specific surface area of kaolinite compared to quartz. Osacky et al stated that the nonswelling clays retained 20–58% of solvent-insolvable organic materials of the total content, mainly on the basal planes and edges of clays in the form of patches . The amount of organic materials retained after extraction and solvent removal from the tailings correlated well with specific surface area of clays.…”
Section: Solvent Recoverymentioning
confidence: 99%
See 1 more Smart Citation